Analisis Yuridis Pertimbangan Hukum Pada Putusan Wanprestasi Atas Utang Tertunggak: Studi Kasus Putusan Nomor 371/PDT.G/2024/PN MDN - Asseweth, Hamzah Abud; Hidayani, Sri; Siregar, Fitria Yanni Dewi (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This research aims to analyze the application of Article 1320 of the Civil Code in demands for payment of outstanding debts and the judge's considerations in rejecting demands for payment of dwangsom money and immaterial losses and in decision Number 371/PDT.G/2024/PN MDN. The problem of debts and receivables is a complicated problem because the risk that generally occurs is default and must go through a court decision that has legal force. This research uses normative juridical research and methods taken from library research. Based on the research results, the application of Article 1320 of the Civil Code in demands for payment of outstanding debts in Decision Number 371/PDT.G/2024/PN MDN is in accordance with the conditions specified in Article 1320 of the Civil Code because it is based on an agreement between two parties who are competent to act. The judge's consideration in rejecting the claim for immaterial losses and forced payment of money (dwangsom) in Decision Number 371/PDT.G/2024/PN MDN was because the Plaintiff could not prove that there was an urgent reason that had to be carried out which had no legal grounds and had to be rejected. However, claims for dwangsom money and immaterial losses should be applied or considered in this decision because the defendant has committed an unlawful act and legally committed a breach of contract. It is hoped that there will be laws and legal regulations that specifically regulate the implementation of dwangsom (forced money) and immaterial losses.